2011
DOI: 10.1242/jcs.086629
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis and adipogenesis originate from a common mesenchymal progenitor in skeletal muscle

Abstract: SummaryAccumulation of adipocytes and collagen type-I-producing cells (fibrosis) is observed in muscular dystrophies. The origin of these cells had been largely unknown, but recently we identified mesenchymal progenitors positive for platelet-derived growth factor receptor alpha (PDGFRa) as the origin of adipocytes in skeletal muscle. However, the origin of muscle fibrosis remains largely unknown. In this study, clonal analyses show that PDGFRa + cells also differentiate into collagen type-I-producing cells. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
601
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(622 citation statements)
references
References 38 publications
18
601
0
3
Order By: Relevance
“…Analysing both polyclonal and monoclonal cell cultures, we could not identify any MP subpopulation with adipogenic potential. Our results further support previous work showing that MPs are committed to the myogenic fate30, 31, 49, 51 and that FAPs are the adipocyte precursor population residing in murine30, 31, 32, 52 and human24, 51, 53, 54 adult skeletal muscle. Although we cannot reject the hypothesis that a small subpopulation of satellite cells could form brown adipocytes—as shown by Yin et al 27.…”
Section: Discussionsupporting
confidence: 92%
“…Analysing both polyclonal and monoclonal cell cultures, we could not identify any MP subpopulation with adipogenic potential. Our results further support previous work showing that MPs are committed to the myogenic fate30, 31, 49, 51 and that FAPs are the adipocyte precursor population residing in murine30, 31, 32, 52 and human24, 51, 53, 54 adult skeletal muscle. Although we cannot reject the hypothesis that a small subpopulation of satellite cells could form brown adipocytes—as shown by Yin et al 27.…”
Section: Discussionsupporting
confidence: 92%
“…Uezumi et al reported that PDGFRα‐positive mesenchymal progenitors are the major contributor to ectopic fat cell formation in skeletal muscle 21. Moreover, they suggested that mesenchymal progenitors are the main origin of not only fat accumulation but also fibrosis in skeletal muscle 22. Adipogenic transcription factors have been considered key regulators for fatty degeneration of muscle after RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Although the factors leading to fat accumulation in the muscle are not yet fully defined, it has been reported that aging, muscle injury, mechanical unloading, and hormonal imbalance are main causes of ectopic fat formation 1, 2, 18, 19, 20. With respect to the molecular mechanism underlying muscle fat accumulation, it has been reported that pluripotent stem cells or progenitor cells residing in the muscle differentiate into adipocytes by the action of adipogenic transcription factors such as CCAAT/enhancer binding protein alpha (C/EBPα) and peroxisome proliferator activated receptor gamma (PPARγ) 8, 21, 22. Previous studies have suggested that rotator cuff fatty infiltration is also mediated by these adipogenic transcription factors 8, 23, 24, 25.…”
Section: Introductionmentioning
confidence: 99%
“…One study that isolated rat serum following severe burns (40% total surface area) and applied it to satellite cell cultures found enhanced cell proliferation, migration and osteogenic differentiation [61]. However, more recent studies suggest that the image of a satellite cell as a multipotent cell type capable of contributing to osteochondrogenic differentiation may be untrue, with some authors claiming that any non-myogenic differentiation observed in these cultures potentially results from contamination with other stem/progenitor cells obtained during myofibre isolation [62,63]. In fact, a number of studies can be found that claim satellite cells are committed to the myogenic lineage, and as such are crucial for muscle regeneration following injury but unlikely to contribute to the formation of ectopic bone seen in HO [64,65].…”
Section: Satellite Cellsmentioning
confidence: 99%